Aloe vera as a treatment of reccurent aphtousa stomatitis: Penggunaan Aloe vera sebagai perawatan reccurent aphtousa stomatitis - Egita Aprilia Sukarno; Nur Asmi Usman (Makassar Dental Journal PDGI Makassar, 2023)
Recurrent aphtousa stomatitis (RAS) is a self-limiting disease that can affect the patient's daily quality of life because it can cause difficulty speaking, swallowing and eating. For this reason, treatment is needed to reduce the degree of pain or inflamma-tion and increase the duration of healing, one of which is using aloe vera. This article examines the effectiveness of aloe vera as a remedy for RAS. Scientific information appropriate to the study topic was collected from Pubmed, Elsevier and Science Direct databases and synthesised into literature review articles. Of the 5 articles synthesised, there were similarities in the dis-cussion of the effectiveness of aloe vera as a treatment for RAS. It was concluded that aloe vera is considered effective in short-ening the healing time of RAS up to 7 days.